An Asymmetric Investigation of Remittance and Trade Openness Impact on Inequality: Evidence From Selected South Asian Countries - Fang, Liu; Qamruzzaman, Md. (Frontiers in Psychology, 2021)
This study's motivation is to explore the pattern of the relationship between Remittance, Trade openness, and inequality of selected south Asian countries for the 1976-2018 periods. The study performed nonlinear tests, including unit root tests, nonlinearity applying OLS and BDS test, nonlinear autoregressive distributed lagged (NARDL), and asymmetry causality test to assess their association. Study findings with nonlinear unit root tests suggested that the research variables follow the nonlinear process of becoming stationary from nonstationary. The Nonlinear OLS and BDS test results confirm the existence of nonlinearity among research variables, implying that rejecting the null hypothesis of "no nonlinearity." Furthermore, the results of the Wald test in NARLD confirm the availability of asymmetric links among variables. Besides, the results of NARDL confirmed the long-run asymmetric relationship between remittance, trade openness, and inequality. Findings suggest that both positive and negative shocks in remittance and tread openness are critical to either instituting or vexing the present state of the economy in the long term. In the directional relationship with asymmetry causality, t showed that the feedback hypothes holds positive shocks in remittance and trade openness towards inequality.